The synergistic depression of lime and sodium humate on the flotation separation of sphalerite from pyrite. (15th March 2021) - Wei, Qian; Dong, Liuyang; Jiao, Fen; Qin, Wenqing; Pan, Zuchao; Cui, Yanfang
Highlights: Mixed depressant CaO/NaHA could achieve the flotation separation of sphalerite from pyrite. The adsorption of CaO/NaHA is stronger on pyrite surface than that on sphalerite surface. NaHA may mainly react with pyrite surface through Ca atoms in the presence of CaO. A possible adsorption mechanism is finally obtained. Abstract: Pyrite depression in flotation separation of Zn-S mixed concentrate has become a difficult and serious problem. This work introduces a non-toxic and efficient depressant reagent scheme in selective flotation separation of spalerite from pyrite with pretreatment by CuSO4 and butyl xanthate (BX). Micro-flotation experiments showed that the combined depressant lime (CaO) and sodium humate (NaHA) depressed the floatability of pyrite more strongly than that of the sphalerite within at pH 11.5–12.0. Moreover, the inhibitory effect of NaHA on pyrite was significantly promoted by calcium-species dissolved from CaO. Real ore sample flotation separation tests showed that the mixed depressant CaO and NaHA acted better than single depressant CaO or NaHA, and the best results were obtained by addition of 850 g/t CaO and 30 g/t NaHA at pH 11.5, with 46.01% Zn grade and 90.11% Zn operating recovery. The synergistic depressing mechanism of CaO and NaHA was revealed through adsorption amount measurements, contact angle measurements, fourier infrared spectroscopic (FT-IR) analysis and X-ray photoelectron spectroscopy (XPS) analysis. Mechanism experiments indicated that the addition of calcium species (mainly as Ca 2+ and Ca(OH) + ) promoted the adsorption of NaHA on mineral surfaces, and the pyrite surface adsorbed much more calcium-species and NaHA than that of the sphalerite. The chemical adsorption of NaHA on pyrite was mainly through its carboxyl groups and Ca atoms on pyrite surface, while the NaHA adsorption on sphalerite surface was relatively weak.